1989
DOI: 10.1104/pp.89.1.333
|View full text |Cite
|
Sign up to set email alerts
|

Seed Development in Phaseolus vulgaris L. cv Seminole

Abstract: Phaseolus vulgaris L. cv Seminole pods removed from the plant continued their development when incubated in suitable conditions. Seeds continued to grow and develop and pods and seeds passed through an apparently normal developmental sequence to dryness. Seed growth was at the expense of pod dry weight (DW) reserves. Losses of pod DW paralleled DW gains by seeds in detached pods and in pod cylinders containing a seed. The transfer activity was apparent only within the period 10 to 30 days after anthesis (DAA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…By 20–25 DAF, pods have reached their final size ( Fountain et al, 1989 ), and fruit growth is mainly associated with the active accumulation of storage materials in seeds ( Figure 1A ). In fruits removed from the plant at 20 DAF, seeds can growth at the expense of the nutrients provided for the pod.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By 20–25 DAF, pods have reached their final size ( Fountain et al, 1989 ), and fruit growth is mainly associated with the active accumulation of storage materials in seeds ( Figure 1A ). In fruits removed from the plant at 20 DAF, seeds can growth at the expense of the nutrients provided for the pod.…”
Section: Resultsmentioning
confidence: 99%
“…This process is normally associated with leaf senescence, where most of the available nutrients are transported to developing seeds ( Yang et al, 2001b ), but materials accumulated in stems and pods are also important for seed development ( Schiltz et al, 2005 ). Seeds of Phaseolus vulgaris can continue their development at the expense of pod reserves when the fruits are removed from the plant at 15–25 days after flowering (DAF; Fountain et al, 1989 ). SnRK1 has been identified as an important component in the mechanism that allows plants to respond to C and energy deficiencies ( Schluepmann et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, results from depodding experiments showed that, under incubation, pods removed before the maximum length is reached do not persist, while pods harvested after this point produce viable seeds (Fountain et al . ). Very similar synchronization patterns have been reported for determinate and indeterminate bean cultivars (Oliker et al .…”
Section: Discussionmentioning
confidence: 97%
“…The reproductive developmental patterns of the common bean have been widely studied (Binnie & Clifford , ; Lovett‐Doust & Eaton ; Pechan & Webster ; Fountain et al . ; Muasya et al . ).…”
Section: Introductionmentioning
confidence: 99%